Produção de grês porcelanato a partir de matérias-primas do Rio Grande do Norte e queima a gás natural - Pinheiro, Andréa Santos (2006)
The State of Rio Grande do Norte, Brazil, possess major deposits of feldspar, clay, kaolin and talc, all raw materials used in the production of porcelainized stoneware tiles. Conversely, state industries manufacture only low added value red ceramics. Porcelainized stoneware tiles is one of the noblest ceramics, depicting low water absorption (typically below of 0,5%), in addition to excellent staining resistance and mechanical strength. The present work aims at investigating the potential of local raw materials for the production of porcelainized stoneware tiles. To that end, these materials were characterized by X-ray fluorescence, X-ray diffraction, particle size analysis, thermal gravimetric analysis and thermal differential analysis. Admixtures containing different compositions were prepared and fired at three temperatures, 1150, 1200 and 1250°C for 30 min. After firing, tests samples were characterized by water absorption tests, linear retraction, dilatometric analysis, apparent porosity, apparent specific mass, flexural strength, and microstructural analysis by XRD and SEM. The results revealed that ceramics with porcelainized stoneware tiles characteristics could be produced from raw materials originated in the State of Rio Grande do Norte